La desorganización familiar y su relación con el desarrollo de habilidades sociales de los niños y niñas del primer grado de educación general básica de la escuela Gabriela Mistral n°1 del cantón Catamayo, provincia de Loja, periodo 2013 – 2014. Lineamientos alternativos - Rivas Paladinez, Jeomar Esperanza (2014)
This research work, called the "FAMILY DISRUPTION AND ITS RELATION TO THE DEVELOPMENT OF SOCIAL SKILLS OF CHILDREN FIRST GRADE OF GENERAL BASIC EDUCATION SCHOOL "GABRIELA MISTRAL No. 1" CATAMAYO CANTON, Loja Province, PERIOD 2013 - 2014" ALTERNATIVE GUIDELINES. It has been structured and developed in accordance with the Rules of the Academic Board of the National University of Loja. The General objective was formulated to determine the incidence of Family Disorganization in the Development of Social Skills of Children First Grade Basic Education. The methods used were the Scientific, Descriptive, Analytical Method - Synthetics and Statistical Model, techniques that were applied are the survey and observation sheet for data collection and processing framework. The survey of Parent, to establish the Family Disorganization; and the observation sheet to children in First Grade General of Basic Education "Gabriela Mistral N° 1" School Catamayo Canton, to assess the development of Social Skills. From 100% Parents, the 54% says that the main characteristic of family disorganization is separation, divorce 32% and 14% being widowed. Family disorganization is the breakdown of the family unit, caused by separation and divorce and consequently widowed; these situations break the family structure, and therefore fail to fulfill the duties and obligations to each responsibility. To establish the causes of family disorganization 33% Parents have a drinking problem. Alcoholism is a social evil that contributes to leaving home, the misuse of funds and unemployment. The 28 % are low income. The economic factor occurs when altered critical periods throughout the marriage. And, the 28% by migration. Migration is the output of one of the spouses forming the pair outwards in search of a better economic return. The 44% of boys and girls have evaluated Social Skills Development Satisfactory, 35% Very Satisfactory and Unsatisfactory 20%. Children First Grade has the Development of Social Skills Satisfactory at finding that family disruption is related to the development of social skills of the students evaluated. Social Skills are that give the girl child and the ability to interact with their peers in a given social context and an accepted way socially and personally beneficial or valued.